Dynamic behavior of single-phase natural convection loops integrated to a pool - Lima, Leon Matos Ribeiro de (2016)
Passive cooling systems find application on many areas of engineering. Nuclear power industry is incorporating such systems in new power plant designs, with the objective of achieving higher levels of safety. Natural convection loops are passive cooling systems consisting of two heat exchangers a heater and a cooler and a connecting circuit, where heat is absorbed in the heater and rejected in the cooler. In most of designs, the circuit is connected to a pool which transfers heat from it, if connected to the cooler, or to it, if connected to the heater. Natural convection loops are the research topic of many scientific works. The connection to the pool, however, is not taken into account. The present work presents a computational study of the dynamic behavior of single-phase natural convection with a pool integrated to the heater, with focus on the thermo-hydraulic stability. Linear and non-linear analyses are performed in order to characterize the system dynamics. Results indicate a relevant contribution of the pool, significantly enlarging stability regions.